Job descriptions, from conception to recruitment: A qualitative review of hiring practices - Kimberly Seung Goulart; Jorge Rodríguez Menés; Josep Maria Caroz Armayones (European Commission, Joint Research Centre (JRC), 2022)
The shift from an industrial economy to a knowledge and service economy over the last four decades has ignited a debate about what skills are now the most critical. The European Commission has placed skills development at the heart of its economic policies, as it believes that skill mismatches can lead to high unemployment rates, increased inequalities, and hindered innovation and corporate investment. However, more evidence is needed about how firms define new skills and workers' core competences, and communicate their needs to jobseekers. This article takes a qualitative approach and adds insights into this process from the firm perspective. Through 14 interviews with human resource professionals, we observed that the processes for identifying, defining, and evaluating skills and competences differ greatly by job profile and seniority, as well as firm size. We also found that within our sample, "soft" and "transversal" skills were equally regarded and relied on heavily during the selection phase of the recruitment process. The practice of firms to define new and specialised competences by the tools and methods used to carry out the job was also widespread. These findings are a first step in improving our understanding of the firm's recruitment process and talent acquisition.
Keywords: 330; Human resources; skills and competences; job analysis